TINJAUAN SISTEMATIS TENTANG PERAN SISTEM WHISTLEBLOWING DAN PENGENDALIAN INTERNAL DALAM PENCEGAHAN KECURANGAN - Marican, Najwa (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2025)
This research aims to systematically examine the contribution of whistleblowing systems and internal controls in preventing fraud in the public and private sectors in Indonesia. The method applied is a Systematic Literature Review (SLR), with a search for relevant literature through the SINTA database from 2019 to 2024. The article selection process was conducted in two stages: exploration of the number of articles and filtering based on relevance, resulting in 15 articles that met the criteria. The results show that whistleblowing systems and internal controls support each other in fraud prevention. Of the 15 articles analyzed, 47% discussed whistleblowing systems, 33% focused on internal controls, and 20% related to fraud prevention. The implementation of solid internal controls and an effective whistleblowing system can significantly reduce the risk of fraud. This research provides valuable perspectives for organizations in developing and strengthening whistleblowing systems and internal controls, thereby creating a more transparent and accountable environment and reducing the potential for fraud. This research presents a comprehensive review of the existing literature, filling gaps in the understanding of the relationship between whistleblowing systems and internal controls, and offering practical recommendations for more effective implementation in Indonesia. Keywords; whistleblowing, internal control, condition prevention